Towards Democratizing and Automating Online Conferences: Lessons from the Neuromatch Conferences. Issue 4 (April 2021) - Achakulvisut, Titipat; Ruangrong, Tulakan; Mineault, Patrick; Vogels, Tim P.; Peters, Megan A.K.; Poirazi, Panayiota; Rozell, Christopher; Wyble, Brad; Goodman, Dan F.M.; Kording, Konrad Paul
Abstract : Legacy conferences are costly and time consuming, and exclude scientists lacking various resources or abilities. During the 2020 pandemic, we created an online conference platform, Neuromatch Conferences (NMC), aimed at developing technological and cultural changes to make conferences more democratic, scalable, and accessible. We discuss the lessons we learned.